Temperature and doping-tuned coordination environments around electroactive centers in Fe-doped α(β)-Ni(OH)2 for excellent water splitting. Issue 3 (16th January 2020) - Cao, Qinghe; Luo, Mi; Huang, Yutian; Liu, Qi; Kong, Xiaoxing; Lei, Jinlong; Jiang, Zheng; Wang, Jiahai
Abstract : β-Ni(OH)2 on Ni foam can be synthesized using a hydrothermal method. The addition of Fe 3+ during synthesis produced Fe-doped α-Ni(OH)2 at 120 °C and Fe-doped β-Ni(OH)2 at 240 °C. The HER and OER activity of these materials were investigated through both experiment and DFT. Abstract : In this study, Fe-doped β-Ni(OH)2 exhibited an unpredictable hydrogen evolution reaction (HER) performance, which is much better than that of Fe-doped α-Ni(OH)2 . Meanwhile, Fe-doped α-Ni(OH)2 showed a much better oxygen evolution reaction (OER) than Fe-doped β-Ni(OH)2 . At 120 and 240 °C, Fe-doped α-Ni(OH)2 and Fe-doped β-Ni(OH)2 are synthesized, respectively, by the addition of Fe 3+ into a hydrothermal solution immersed with nickel foam. The higher valence of Ni and Fe in the α-phase benefits the OER performance. In contrast to the α-phase case, the enrichment of the electron cloud around Fe in the β-phase due to surrounding coordination environment is conducive to the HER, which can be verified consistently from XPS, XAFS, XANES and DFT. By taking Fe as the active sites, DFT calculations have confirmed that the energy barrier for each step of the HER is much lower than that corresponding to the Ni site. Only a 53.8 mV overpotential for Fe-doped β-Ni(OH)2 -240 is needed to achieve a current density of 10 mA cm −2, which is comparable with most of the active HER electrocatalysts. The electrolyzer cell employing Fe-doped β-Ni(OH)2 -240 as the cathode and Fe-doped α-Ni(OH)2 -120 as the anode demonstrates superior performance for overall water splitting with excellent stability.